The NP-strategy for expressing reciprocity typology, history, syntax and semantics - Bar-Asher Siegal, Elitzur A. (Typological studies in language ;, 2020)
"This book provides a comprehensive treatment of the syntax and semantics of a single linguistic phenomenon - the NP-strategy for expressing reciprocity - in synchronic, diachronic, and typological perspectives. It challenges the assumption common in the typological, syntactic, and semantic literature, namely that so-called reciprocal constructions encode symmetric relations. Instead, they are analyzed as constructions encoding unspecified relations. In effect, it provides a new proposal for the truth-conditional semantics of these constructions. More broadly, this book introduces new ways of bringing together historical linguistics and formal semantics, demonstrating how, on the one hand, the inclusion of historical data concerning the sources of reciprocal constructions enriches their synchronic analysis; and how, on the other hand, an analysis of the syntax and the semantics of these constructions serves as a key for understanding their historical origins"--